Respuesta :

For x = 3 and b = 4 the expression becomes -11

Explanation:

Here we have the following expression and let's name it E:

[tex]E=-5x+b[/tex]

Here we have two variables, namely x and b. In order to evaluate this expression let's set some values for x and b:

[tex]Let's \ say \ x=3 \ and \ b=4: \\ \\ E=-5x+b \\ \\ E=-5(3)+4 \\ \\ E=-15+4 \\ \\ \boxed{E=-11}[/tex]

Finally, for x = 3 and b = 4 the expression becomes -11

Learn more:

Distributive property: https://brainly.com/question/10794694

#LearnWithBrainly